Antisocial Behavior as a Longitudinal Predictor of Somatization in Adolescents - Espejo-Siles, Raquel (Victims & offenders, 2023)
Antisocial behavior and somatization are common problems in schools that have several consequences. However, the relation among these problems is not clear. This longitudinal research aims to better understand whether antisocial behavior is related to and predicts somatization, in order to prevent and reduce both disorders in young people. A longitudinal study with a one-year follow-up was carried out with students from several schools in Spain (N = 384). Validated questionnaires were used to assess antisocial behavior and somatization. Descriptive, correlational and linear regression analyses were performed. Most of the antisocial behaviors had significant correlations with somatization in both waves of the study. High scores in theft, violence and substance use were related to high scores in somatization cross-sectionally and one year later, in boys and girls. Female gender, high scores in violence and high scores in status offenses were related concurrently to more somatic symptoms. Female gender, high scores in violence and high scores in substance use predicted more somatic symptoms one year later. Antisocial behavior was found to be highly related to somatization. Early substance use prevention programs and programs to decrease violence at school could help reduce substance use, violence and somatization in students.